GRUBOŚĆ POKRYWY LODOWEJ WYBRANYCH JEZIOR O GENEZIE EOLICZNEJ, KRASOWEJ I RZECZNEJ W WOJEWÓDZTWIE ŚWIĘTOKRZYSKIM - ZIELIŃSKI, ARTUR; CHOIŃSKI, ADAM (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2021)
The research covered three genetic groups of lakes (karst, aeolian, and riverine) which occur in Świętokrzyskie Voivodeship. Depending on the specific group, the lakes have different morphometric parameters of the lake basin and the water catchment area as well as physical and chemical properties of the water. In winter 2021, after a wave of severe frost, the thickness of the ice was measured on a selected number of lakes. The results of the tests indicate a diverse thickness of the ice caps. Karst lakes had the thickest ice caps. Riverine and aeolian lakes, on the other hand, featured similar thickness of the ice. However, it was noticed that in the case of riverine lakes, the ice cap on shores with prevailing reed was thinner than in the central parts of the lake.